Valla’s False Modesty: The Annotationes Novi Testamenti Compared with the Biblical Scholarship of Giannozzo Manetti (1396–1459) and Aurelio Lippi Brandolini (1454?–1497) - den Haan, Annet (2023)
The Italian humanist Lorenzo Valla (1406–1457) wrote his Annotationes Novi Testamenti in Rome and Naples in the 1440s and 1450s. According to Valla’s own writings, the aim of this work was to cleanse the Latin Bible of textual corruptions and to clarify obscurities and inaccuracies. He questioned the common belief that the Latin Bible was written by Jerome. This article compares Valla’s reflections on his own project with those of two other fifteenth-century humanists who engaged in biblical scholarship: Giannozzo Manetti (1396–1459) and Aurelio Lippi Brandolini (1454?–1497). Compared to them, Valla’s aim was modest: Manetti and Brandolini never questioned Jerome’s authorship, and yet they competed directly with the Church Father by providing an alternative to the Latin Bible. On the other hand, Valla’s aim may be considered more ambitious, because he directly challenged the Latin Bible as the standard translation of his time.
Keywords: Latin Bible; Biblical Scholarship; Humanism; Aurelio Lippi Brandolini; Giannozzo Manetti; Lorenzo Valla